2014
DOI: 10.1016/j.ejmech.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of largazole analogues with modified surface recognition cap groups

Abstract: Several largazole analogues with modified surface recognition cap groups were synthesized and their HDAC inhibitory activities were determined. The C7-epimer 12 caused negligible inhibition of HDAC activity, failed to induce global histone 3 (H3) acetylation in the HCT116 colorectal cancer cell line and demonstrated minimal effect on growth. Although previous studies have shown some degree of tolerance of structural changes at C7 position of largazole, these data show the negative effect of conformational chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…A few analogues of largazole containing non‐standard amino acid units, including 1‐naphtylmethyl and 1‐allylglycine (Figure ), has been recently reported and tested for enzymatic activities on HDACs 1 and 6, and for growth inhibition of HCT116 colon carcinoma cells . The results obtained further confirmed that heterogeneous aromatic substituents at C2 position of the macrocycle were well tolerated, provided that the proper stereochemistry was maintained.…”
Section: Analogues With Modified Valine Unitmentioning
confidence: 65%
“…A few analogues of largazole containing non‐standard amino acid units, including 1‐naphtylmethyl and 1‐allylglycine (Figure ), has been recently reported and tested for enzymatic activities on HDACs 1 and 6, and for growth inhibition of HCT116 colon carcinoma cells . The results obtained further confirmed that heterogeneous aromatic substituents at C2 position of the macrocycle were well tolerated, provided that the proper stereochemistry was maintained.…”
Section: Analogues With Modified Valine Unitmentioning
confidence: 65%
“…The stereochemical configuration of largazole proved to be crucial for activity, with the C2‐epimer 239 a , the C7‐epimer 239 d , the C17‐epimer 239 c , and the enantiomer 239 b of largazole/largazole thiol showing weaker HDAC inhibitory activity than the parent compounds (Scheme ) . The ability of 239 c and 239 d to inhibit HCT‐116 cell growth has also been evaluated, and a substantially reduced activity relative to largazole was measured …”
Section: Analogues and Structure–activity Relationshipsmentioning
confidence: 99%
“… In vitro and in vivo activity of largazole analogues. [a] Data reported by Tillekeratne and co‐workers . [b] Percent inhibition at 1 μ m inhibitor concentration.…”
Section: Analogues and Structure–activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,3032 In contrast, potent analogues have been generated by structural modification of the depsipeptide ring (surface recognition cap group). 28,30,31,3335 The lower sequence homology between different HDAC isoforms at the surface near the opening to the binding pocket may be exploited to design more potent HDAC inhibitors by targeting the depsipeptide ring. 17 …”
Section: Introductionmentioning
confidence: 99%